2013
DOI: 10.1063/1.4801649
|View full text |Cite
|
Sign up to set email alerts
|

Improved ionic conductivity in strained yttria-stabilized zirconia thin films

Abstract: Yttria-stabilized zirconia (YSZ) thin films with thickness ranging from 6 nm to 100 nm were prepared by RF sputtering on (0001) Al2O3 substrates and exhibited epitaxial growth along (111)[110] YSZ//(0001)[101¯0] Al2O3. While the thicker films exhibited oxygen ion conductivities similar to bulk samples, the thinnest films exhibited increased ionic conductivity and a reduced activation energy of 0.79 eV between 300 °C–650 °C. Concomitant with the improved conductivity of the thinner films is an increase in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 26 publications
3
54
1
Order By: Relevance
“…Figure 4 shows the measured oxygen ionic conductivity versus temperature for VAN films including YSZ and SDC, compared to YSZ films, doped CeO 2 films, and their multilayer films. 11,13,33,[77][78][79][80][81][82] Enhanced ionic conductivity values by one order of magnitude or more are observed. 49,50 Enhancement of ionic conductivity values has also been observed in VAN films of YSZ and Gd-doped CeO 2 .…”
Section: A Resistive Switching Phenomenamentioning
confidence: 94%
“…Figure 4 shows the measured oxygen ionic conductivity versus temperature for VAN films including YSZ and SDC, compared to YSZ films, doped CeO 2 films, and their multilayer films. 11,13,33,[77][78][79][80][81][82] Enhanced ionic conductivity values by one order of magnitude or more are observed. 49,50 Enhancement of ionic conductivity values has also been observed in VAN films of YSZ and Gd-doped CeO 2 .…”
Section: A Resistive Switching Phenomenamentioning
confidence: 94%
“…In this work, GDC films with thicknesses down to 15 nm were prepared on (0001) Al 2 O 3 and characterized with impedance spectroscopy to measure the function of nanoscale thickness on the conductivity. Prior work examining YSZ films deposited and measured using highly similar methods found that sub-100 nm thick films had lattices that were significantly dilated in the out-of-plane direction and supported significantly increased conductivity [15].…”
Section: Introductionmentioning
confidence: 99%
“…The Arrhenius plot for σ t , (b), is not linear, consistent with that reported for various YSZ samples on many other occasions. 3,7,8,10,28,29 This non-linearity is widely attributed to trapping of oxygen vacancies in vacancy-dopant complexes at low temperatures: 30 at higher temperatures, dissociation of the complexes occurs and the trapping enthalpy is not included in the activation energy. The total conductivity, σ t , at high temperatures, would therefore represent the hopping of free vacancies.…”
mentioning
confidence: 99%
“…Many data sets, especially for compositions that exhibit high oxide ion conductivity, show distinct curvature of the Arrhenius plots which is attributed to the trapping at lower temperatures of mobile oxide ion vacancies in vacancydopant defect complexes. 3,[7][8][9][10] Two possible defect complexes that are widely discussed are the charged dimer, (Y Zr V…”
mentioning
confidence: 99%